Characterization of the novel HLA‐A*01:406 allele by two next generation sequencing methods. (3rd January 2022) - Walencik, Alexandre; Calvo De Olmos, Orane; Bonneville, Francoise; Blanchet, Gaelle; Cesbron‐Gautier, Anne
Abstract : The novel HLA‐A*01:406 allele was characterized using two next generation sequencing technologies.